2011
DOI: 10.1021/bk-2011-1090.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Catnip Essential Oil and Its Nepetalactone Isomers as Repellents for Mosquitoes

Abstract: The effect of catnip Nepeta cataria essential oil and two isomers of nepetalactone, the major components, on the distribution of Aedes aegypti (yellow fever mosquito) mosquitoes in a static-air olfactometer response was examined to determine their activity as spatial repellents. A glass cylinder was used as a choice-test chamber. The catnip (Nepeta cataria) essential oil, as well as the E,Z-and Z,E-isomers of nepetalactone were significantly repellent after application of one ml of 1% and 0.1% solution to filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…These results are confirmation of earlier reports by (Sanaa, et al, 2008;Abdullah, et al, 2014 on the use of biopesticides in the management of wood termites. It is evident from these results that extracts did pose a hindrance to activities of the termites (Peterson & Ems-Wilson, 2003;Mao & Henderson, 2007), but the termites, however, may become insensitive towards the extracts upon longer period of exposure and this period depends upon termites species. In order to find out alternative to synthetic insecticides, anti termite properties from plants will continue to expand base of the effective molecules to be developed to go well with the ecology of termites.…”
Section: Discussionmentioning
confidence: 82%
“…These results are confirmation of earlier reports by (Sanaa, et al, 2008;Abdullah, et al, 2014 on the use of biopesticides in the management of wood termites. It is evident from these results that extracts did pose a hindrance to activities of the termites (Peterson & Ems-Wilson, 2003;Mao & Henderson, 2007), but the termites, however, may become insensitive towards the extracts upon longer period of exposure and this period depends upon termites species. In order to find out alternative to synthetic insecticides, anti termite properties from plants will continue to expand base of the effective molecules to be developed to go well with the ecology of termites.…”
Section: Discussionmentioning
confidence: 82%
“…Botanicals from the Lamiaceae family have also demonstrated that their essential oils can act as a mosquito repellent comparable to DEET 41,42 . One member of this family, Nepeta cataria (catnip), has had its essential oils containing various nepetalactone stereoisomers tested and the results showed that it is comparable to DEET at repelling mosquitoes, while offering better spatial repellency 4345 . Nepetalactones are the distinguishing natural compounds associated with catnip and are the euphoria-inducing agent in felines responsible for their characteristic behavior 46 .…”
Section: Introductionmentioning
confidence: 99%
“…i. Medicated net: Medicated nets made up of 25% deltamethrin which made by K-O tablets. One tablet is properly mixes in one litter water for ten minutes and after it dried and placed at chilled area to make medicated nets [38] . Medicated nets life only six months, which is approved by WHO [39] .…”
Section: Physical Methodsmentioning
confidence: 99%